Clinical features associated with macrolides resistance of Mycoplasma pneumoniae pneumonia in children: a single-center analysis - Shuzhen Han; Qiaoxin Fang; Xia Wu; Yingzi Ye; Lijing Ye; Jun Xu; Hui Yu (BMC Infectious Diseases)
Abstract Background To analyze the clinical characteristics and antibiotic resistance of Mycoplasma pneumoniae pneumonia (MPP) children, and explore the clinical features associated with macrolides resistance in MPP patients. Methods We retrospectively collected clinical data of children with MMP from August 2023 to November 2023 at the Department of Infectious Diseases, Children’s Hospital, Fudan University, Shanghai, China. General information, clinical presentation, imaging findings, laboratory findings, and treatment were recorded. We divided our patients into < 5-year-old group or ≥ 5-year-old group, with complication group or without complication group, and gene-mutated group or non-mutated group based on clinical characteristics and compared the differences between groups. Then, we investigated the clinical features associated with macrolides resistance of MPP. Result Of 285 children who had MPP, 161 cases (71.9%) aged ≥ 5 years were more likely to be associated with pleural effusion (P < 0.05), while those aged < 5 years were more prone to exhibit gastrointestinal symptoms (P < 0.05). Among the 250 children (87.7%) with complications, hyperlactatemia was the most common, occurring in 58.6% of cases. In the drug-resistant group, which comprised 224 cases (78.6%), children aged ≥ 5 years accounted for 71.9%. The incidence of hyperlactatemia in the drug-resistant group was 62.5%, and the rate of second-line anti-MP drug usage was 84.8%, both of which were higher than in the non-resistant group (P < 0.05). Being aged ≥ 5 years and having hyperlactatemia may be associated with the risk of macrolides resistance in MMP children, aOR 95%CI: 1.95(1.07, 3.57), 2.28(1.25, 4.17), respectively. But fever was not associated with the risk of macrolides resistance after adjusting factors. Conclusion In conclusion, pediatric cases of MPP were more frequently observed in children aged five years and older, with a notable 78.6% exhibiting drug-resistance gene mutation. The management of patients with resistant cases often involved combination therapy with second-line antibiotics and corticosteroids for the treatment of Mycoplasma pneumoniae. Aged ≥ 5 years and having hyperlactatemia may be associated with the risk of macrolides resistance in MMP children. Clinical trial number Not applicable.